2019
DOI: 10.29333/ejmste/112202
|View full text |Cite
|
Sign up to set email alerts
|

Training Practices of Self-efficacy on Critical Thinking Skills and Literacy: Importance-Performance Matrix Analysis

Abstract: This study, which is rooted in design thinking, explores how participants in both academia and industry settings vary in their perceived self-efficacy in critical thinking after using online training units with information and communication technologies (ICTs). Based on the quasi-experimental pre-post research design with stratified sampling, the researchers completed an empirical validation administered to 739 research participants with a valid return of 75%. Perceived self-efficacy increases critical thinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…However, not all learners can successfully participate in online courses. Several studies have mentioned self-efficacy and its contribution to academic success, especially in satisfaction with online learning (Doo & Bonk, 2020;Jiwa, Tanduklangi, & Sailan, 2017;Kreth, Spirou, Budenstein, & Melkers, 2019;Lin, Hu, & Chiu, 2020). In addition, students' engagement is also regarded as a factor that influences students' satisfaction in online learning (Gray & DiLoreto, 2016;O'Flaherty & Phillips, 2015;Wolverton, Guidry Hollier, & Lanier, 2020).…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all learners can successfully participate in online courses. Several studies have mentioned self-efficacy and its contribution to academic success, especially in satisfaction with online learning (Doo & Bonk, 2020;Jiwa, Tanduklangi, & Sailan, 2017;Kreth, Spirou, Budenstein, & Melkers, 2019;Lin, Hu, & Chiu, 2020). In addition, students' engagement is also regarded as a factor that influences students' satisfaction in online learning (Gray & DiLoreto, 2016;O'Flaherty & Phillips, 2015;Wolverton, Guidry Hollier, & Lanier, 2020).…”
Section: Introduction mentioning
confidence: 99%
“…Through such practice, students would get active mastery experience, which is the essential source of self-efficacy (Lin et al, 2020). Also, the classroom should be a learning atmosphere for students.…”
Section: Introduction mentioning
confidence: 99%
“…One of the studies conducted by Haruehansawasin and Kiattikomol (2018), concluded that students with low levels of PBL learning achievement could benefit from more explicit guidance and encouragement to take a more participatory role in learning. The latest research conducted by Lin et al (2020) which examined the development of scaffolding and teaching simulation tools resulted in the finding that students in the mind scaffolding group showed better learning effectiveness, which was significantly higher than students in the mind scaffolding group. Zhou (2012) stated that this method can stimulate learning motivation and help students form their social identity as creative collaborators.…”
Section: Discussionmentioning
confidence: 99%
“…CT is relevant in any educational setting because it allows individuals should go beyond merely storing more complicated awareness of the information provided to them (Dwyer et al, 2012;Halpern, 2014;Widyatiningtyas et al, 2015). Furthermore, they are also necessary for Social and interpersonal environments where there is a constant need for strong decision-making and problem-solving skills (As'ari et al, 2019;Hage, 2020;Lin et al, 2019). This shows that CT skills are extremely relevant in tackling the 21st-century challenges.…”
Section: Introductionmentioning
confidence: 99%